FOREGIN LINGUISTIC BOUTTYA OF «LEGEND ABOUT SAINTED JULIAN OF MERCIFUL» BY GYOSTAV FLOBER IN TRANSLATION OF VASILIY SHURAT - Lashchic, N. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article is devoted to the analysis of the translated by V. Shurat "Legend about sainted Julian of the Merciful" known French writer of ХІХ age G. Flober. The realizable analysis enables to assert that linguistic translation V. Shurat is almost adequate, is characterized by the correct understanding of maintenance and idea of original source.